The Role of Women's Leadership in Strengthening Quality in Islamic Universities - Purwati, Dwi; Prayitno, Harun Joko; Indri (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study examines the styles and characteristics of women’s leadership in strengthening quality assurance in Islamic higher education institutions and identifies the challenges and strategies involved in institutional change. Using a qualitative two-site multiple-case study design, the research was conducted at Muhammadiyah University PKU Surakarta and ‘Aisyiyah University of Surakarta. Data was collected through semi-structured interviews, participant observation, and document analysis involving key informants from institutional leadership and quality assurance units. Data was analyzed thematically through data reduction, data display, and conclusion drawing and verification. The findings indicate that women leaders in both institutions demonstrate predominantly transformational leadership, characterized by visionary and adaptive direction, empathetic communication, and a sustained commitment to strengthening internal quality assurance systems. Their leadership is reflected in firm yet humanistic governance, integrity in meeting accreditation standards, and active change agency in cultivating a quality culture and improving human resource capacity. Key challenges include resistance to mindset change, uneven human resource capacity, regulatory complexity, digital transformation, and external competitive pressures. Overall, the study highlights women’s strategic capacity to advance institutional quality through collaborative, systematic, and value-based governance in Islamic higher education.